Diaphragm muscle fiber weakness and ubiquitin-proteasome activation in critically ill patients - Hooijman, Pleuni E.; Witt, Christian; Labeit, Siegfried (American journal of respiratory and critical care medicine, 2015)
Rationale: The clinical significance of diaphragm weakness in critically ill patients is evident: it prolongs ventilator dependency, and increases morbidity and duration of hospital stay. To date, the nature of diaphragm weakness and its underlying pathophysiologic mechanisms are poorly understood. Objectives: We hypothesized that diaphragm muscle fibers of mechanically ventilated critically ill patients display atrophy and contractile weakness, and that the ubiquitin-proteasome pathway is activated in the diaphragm. Methods: We obtained diaphragm muscle biopsies from 22 critically ill patients who received mechanical ventilation before surgery and compared these with biopsies obtained from patients during thoracic surgery for resection of a suspected early lung malignancy (control subjects). In a proof-of-concept study in a muscle-specific ring finger protein-1 (MuRF-1) knockout mouse model, we evaluated the role of the ubiquitin-proteasome pathway in the development of contractile weakness during mechanical ventilation. Measurements and Main Results: Both slow- and fast-twitch diaphragm muscle fibers of critically ill patients had approximately 25% smaller cross-sectional area, and had contractile force reduced by half or more. Markers of the ubiquitin-proteasome pathway were significantly up-regulated in the diaphragm of critically ill patients. Finally, MuRF-1 knockout mice were protected against the development of diaphragm contractile weakness during mechanical ventilation. Conclusions: These findings show that diaphragm muscle fibers of critically ill patients display atrophy and severe contractile weakness, and in the diaphragm of critically ill patients the ubiquitin-proteasome pathway is activated. This study provides rationale for the development of treatment strategies that target the contractility of diaphragm fibers to facilitate weaning.